A randomized, waiting list-controlled 12-week trial of atomoxetine in adults with ADHD - Sobanski, Esther; Dittmann, Ralf; Skopp, Gisela; Strohbeck-Kühner, Peter (Pharmacopsychiatry, 2012)
Background: With the increasing recognition of adult attention-deficit/hyperactivity disorder (ADHD) there is an emerging need to investigate medication in this population. Methods: In this waiting list-controlled trial, 64 ADHD-patients (mean age 35.8±8.7 years) were randomly assigned to a daily dosage of up to 80 mg atomoxetine (Atx) or waiting list for 12-weeks. Primary outcome was the change of the observer-rated DSM-IV total ADHD score on the Conners’ Adult ADHD Rating Scales (CAARS-O:L DSM-IV total ADHD score) from baseline to endpoint. Other efficacy measures included self-rated CAARS-S:L DSM-IV total ADHD score, CAARS-O/S:L problems with self-concept and emotional lability score, Wender-Reimherr Adult Attention Deficit Disorder Scale Emotional Dysregulation Score, and General Activities Score on the Quality of Life Enjoyment and Satisfaction Questionnaire. Efficacy measures were analysed in the per-protocol population. Results: Mean change in CAARS:O-L DSM-IV total ADHD score was  - 13.1±7.7 in the Atx vs.  - 0.4±4.8 in the control group (p<0.005). Treatment response (≥30% reduction) was 60.1% in the Atx vs. 0% in the waiting list group. The other efficacy measures also showed significant improvements. The overall incidence of adverse events (AEs) was 70.4% in the Atx group, the most frequent included fatigue, irritability, nausea and decreased appetite. In Atx-treated patients 18.5% discontinued early due to AEs. Discussion: Our results suggest that Atx is an effective treatment in adult ADHD. It reduces ADHD core and associated emotional symptoms and increases self-esteem and quality of life. AEs were consistent with those reported in other studies in adult ADHD.
Published online ahead of print: 15 December 2011
Gesehen am 07.06.2018